In situ investigation of the mechanochemically promoted Pd–Ce interaction under stoichiometric methane oxidation conditions. Issue 2 (20th December 2022) - Danielis, Maila; Divins, Núria J.; Llorca, Jordi; Soler, Lluís; Garcia, Xènia; Serrano, Isabel; Betancourt, Luis E.; Xu, Wenqian; Rodríguez, José A.; Senanayake, Sanjaya D.; Colussi, Sara; Trovarelli, Alessandro
Abstract : A stable Pd 0 /Pd 2+ arrangement generated on Pd/CeO2 prepared by mechanochemistry enables high methane activation rates in the absence of excess oxygen being available. Abstract : The optimization of the supported Pd phase for CH4 activation on Pd/CeO2 catalysts has been a matter of great interest in the recent literature, aiming at the design of efficient methane abatement catalysts for Natural Gas fueled Vehicles (NGVs). Under lean conditions, a mixed Pd 0 /PdO combination has been indicated as exhibiting the best performance, while controversial results have been reported under stoichiometric conditions depending on the support oxide, where either Al2 O3 or zeolite-based supports are usually considered. Here, by means of synchrotron-based in situ NAP-XPS and XRD measurements, we follow the evolution of Pd species on Pd/CeO2 samples prepared by dry mechanochemical synthesis (M) under stoichiometric CH4 oxidation feed, unravelling a stable Pd 0 /Pd 2+ arrangement in a close to 1 : 1 ratio as the most active palladium state for CH4 activation when excess oxygen is not available, in contrast to what was reported for Pd/alumina materials, where metallic Pd 0 nanoparticles showed the highest activity. The combination of NAP-XPS analysis and activity test results highlights the promotional effect of the Pd–Ce interaction, resulting in enhanced oxygen transfer and improved activity and stability of the Pd/CeO2 catalyst prepared by a novel mechanochemical approach even under low O2 content, large excess of water vapor (10 vol%) and high temperature exposure (>700 °C).